(untitled) (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. The article is devoted to the issues of organizational design of the activity of the local self-government body. The article systematizes scientific approaches to the consideration of organizational design. Recommendations for the use of modern technologies of organizational design in the activities of local governments, including tools for modeling the organizational maturity of the organization, which is widely used by business structures are there. Goal. The purpose of this article is to systematize scientific approaches to the design and organizational activities of local governments and outline areas of implementation of modern technologies of organizational design in the practice of local government. Results. It is substantiated that in the conditions of decentralization to ensure effective interaction of subjects and objects of local self-government it is necessary to use modern technologies of organizational design. It is proved that organizational activity is an important component of the activity of a local self-government body, due to which the most important powers of local representative bodies are realized. Scientific approaches to the consideration of organizational design are analyzed. Emphasis is placed on the fact that the technology of organizational design in public administration is both management technology and a tool for developing and implementing organizational innovations in the practice of management of public sector bodies and institutions. It is proposed to use, along with the already existing traditional methods of organizational design (expert, structuring goals, analogies, organizational modeling) tools for modeling the technological maturity of the organization, used in the practice of organizing the activities of business structures. Recommendations for the implementation of organizational maturity models in the practice of local government management have been developed and certain limitations on the possibilities of their application to assess the level of organizational maturity of local governments have been identified. The article presents an adapted model of organizational maturity for organizational design in local government.